Investigating the impact of video games on high school students’ engagement and learning about genetics - Annetta, Leonard A.; Minogue, James; Holmes, Shawn Y.; Cheng, Meng-Tzu (Computers and education, 2009)
The popularity of video games has transcended entertainment crossing into the world of education. While the literature base on educational gaming is growing, there is still a lack of systematic study of this emerging technology’s efficacy. This quasi-experimental study evaluated a teacher created video game on genetics in terms of its affective and cognitive impact on student users. While statistical results indicated no differences ( p > .05) in student learning as measured by our instrument, there were significant differences ( p < .05) found in the participants’ level of engagement while interfacing with the video game. Implications on this emerging line of inquiry are discussed.